2011
DOI: 10.5694/j.1326-5377.2011.tb03263.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the addition of integrated cognitive behaviour therapy and motivational interviewing improve the outcomes of standard care for young people with comorbid depression and substance misuse?

Abstract: Objective: To determine whether the addition of cognitive behaviour therapy and motivational interviewing (CBT/MI) to standard alcohol and other drug (AOD) care improves outcomes for young people with comorbid depression and substance misuse. Participants and setting: Participants were young people with comorbid depression (Kessler Psychological Distress Scale score ≥ 17) and substance misuse (mainly alcohol and/or cannabis) seeking treatment at two youth AOD services in Melbourne, Australia. The study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 26 publications
0
39
0
2
Order By: Relevance
“…For seven studies (eight comparisons [24,[56][57][58][59][60][61]), we could assess the impact of CBT/MI on depressive symptoms at a follow-up measurement 6-12 months posttreatment. A similar small effect size (g = 0.26, 95% CI = −0.01 to 0.54; random-effects model) was found, but with only a trend towards significance and with a high level of heterogeneity (P = 0.063, I 2 = 65.433).…”
Section: Follow-up Assessmentsmentioning
confidence: 99%
“…For seven studies (eight comparisons [24,[56][57][58][59][60][61]), we could assess the impact of CBT/MI on depressive symptoms at a follow-up measurement 6-12 months posttreatment. A similar small effect size (g = 0.26, 95% CI = −0.01 to 0.54; random-effects model) was found, but with only a trend towards significance and with a high level of heterogeneity (P = 0.063, I 2 = 65.433).…”
Section: Follow-up Assessmentsmentioning
confidence: 99%
“…While there are no studies that have specifically looked at the impact of phototherapy on SUD, high rates of comorbid depression and anxiety (Hides et al, 2011) and the negative impacts these disorders have on treatment outcomes suggest a possible role for phototherapy in this group of patients.…”
Section: Treatment Goalsmentioning
confidence: 99%
“…Several studies have combined MI and CBT interventions. The majority of MI-CBT studies focused on behavioural issues such as alcoholism or gambling, and are reported elsewhere (Greenwald 2002, Hides et al 2011). There are a few studies of MI-CBT in challenging clinical conditions.…”
Section: Combining MI and Cognitive Cbtmentioning
confidence: 99%